Pemetaan Jamban Sehat di Kelurahan Babau Kecamatan Kupang Timur Kabupaten Kupang - Elenna Magdalena Reke; Junias, Marylin Susanti; Sahdan, Mustakim; Sintha L. Purimahua (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
A latrine is a structure used for disposing of and collecting human waste in a designated place to prevent it from becoming a source of disease. Latrine sanitation is influenced by the construction of the latrine, the availability of facilities such as clean water, soap, cleaning tools, and the condition of the fecal storage area. This study aims to describe the results of healthy latrine mapping in Babau Subdistrict, East Kupang District, Kupang Regency, East Nusa Tenggara Province. This research is descriptive with a survey approach. The focus of the study includes the condition of latrine buildings, latrine facilities, and fecal storage areas. The research was conducted in Babau Subdistrict, which has a population of 4,229 people and 915 households. Among these, 825 households use goose-neck latrines, 22 households use sloping latrines, 11 households use pit latrines, and 57 households do not have private latrines and instead use shared latrines. The research instruments included observation sheets, a global positioning system (GPS Garmin eTrex 10) location map, photography tools, and QGIS. The results showed that 58.6% of latrine buildings met the required standards, 64.4% of facilities complied with sanitation requirements, and 56.3% of fecal storage areas met the standards. These findings indicate that a significant portion of latrines do not meet the required standards. Therefore, interventions are needed to improve sanitation quality, particularly by enhancing latrine structures, providing adequate facilities, and ensuring a safe and healthy waste disposal system for the community.